The Impact of Injector-Based Contrast Agent Administration on Bolus Shape and Magnetic Resonance Angiography Image Quality. (18th April 2017) - Jost, Gregor; Endrikat, Jan; Pietsch, Hubertus
Objective: To compare injector-based contrast agent (CA) administration with hand injection in magnetic resonance angiography (MRA). Methods: Gadobutrol was administered in 6 minipigs with 3 protocols: (a) hand injection (one senior technician), (b) hand injection (6 less-experienced technicians), and (c) power injector administration. The arterial bolus shape was quantified by test bolus measurements. A head and neck MRA was performed for quantitative and qualitative comparison of signal enhancement. Results: A significantly shorter time to peak was observed for protocol C, whereas no significant differences between protocols were found for peak height and bolus width. However, for protocol C, these parameters showed a much lower variation. The MRA revealed a significantly higher signal-to-noise ratio for injector-based administration. A superimposed strong contrast of the jugular vein was found in 50% of the hand injections. Conclusions: Injector-based CA administration results in a more standardized bolus shape, a higher vascular contrast, and a more robust visualization of target vessels.